2012
DOI: 10.1055/s-0032-1327897
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Melanin Synthesis by the Phenolic Constituents of Sappanwood (Caesalpinia sappan)

Abstract: Introduction !Melanin is a biopigment synthesized in melanosomes. Melanosomes enclosing melanin polymers are transferred from melanocytes to surrounding keratinocytes in the human epidermis. The color of human skin is determined primarily by the quantity, type, and distribution of melanin in keratinocytes [1,2]. Melanin has a critical role in the protection of the skin from solar ultraviolet (UV) radiation [3], but excess synthesis of melanin leads to hyperpigmentation disorders such as melasma, lentigo, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 25 publications
0
32
1
1
Order By: Relevance
“…The above evidence suggested the presence of two C6-C3 units arising both from a neolignan and a glucose moiety, which was supported by analysis of the 13 C NMR, COSY, and HMBC spectra. One and two-dimensional NMR techniques (DEPT, COSY, HMQC, and HMBC) permitted assignments of all the 1 H and 13 C NMR signals for 1 (l " Table 1 and 2). The HMBC correlation peaks of H-8 and C-4′ and the anomeric proton resonance of glucose H-1′′ to C-9′ indicated that compound 1 was an 8-O-4′-neolignan-9′-glucopyranoside.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above evidence suggested the presence of two C6-C3 units arising both from a neolignan and a glucose moiety, which was supported by analysis of the 13 C NMR, COSY, and HMBC spectra. One and two-dimensional NMR techniques (DEPT, COSY, HMQC, and HMBC) permitted assignments of all the 1 H and 13 C NMR signals for 1 (l " Table 1 and 2). The HMBC correlation peaks of H-8 and C-4′ and the anomeric proton resonance of glucose H-1′′ to C-9′ indicated that compound 1 was an 8-O-4′-neolignan-9′-glucopyranoside.…”
Section: Resultsmentioning
confidence: 99%
“…Melanin, the major pigment of skin, plays an important role in protecting it against the harmful effects of UV-irradiation. However, an increase in the levels of epidermal melanin synthesis and its uneven distribution can cause esthetic problems such as freckles, melasma, and aging spots [13]. Melanin synthesis is controlled by a cascade of enzymatic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, skin cleaning products are available on the market from macro-to nanosize containing both synthetic and natural products. 84,85 Research is being performed on several phyto-based nanocompounds for enhanced skin cleaning. Recently, phyto-based extracts used in cleansers showed enhanced skin cleansing activity by reducing pore size and skin oil content.…”
Section: Nanoskin Cleansermentioning
confidence: 99%
“…The heartwood of C. sappan has been used since ancient times as an ingredient in food and folk medicines against bacterial diseases and anemia and as a blood tonic (Tewtrakul et al, 2015;Nirmal et al, 2015). Many bioactive compounds have been derived from C. sappan, including phenolic compounds such as chalcones, protosappanin, brazilin, and homosioflavonoids (Jung et al, 2015;Mitani et al, 2013). 3-Deoxysappanchalcone is a naturally occurring chalcone compound isolated from C. sappan Linn.…”
Section: Introductionmentioning
confidence: 99%